THE EFFECT OF CARBON AND NITROGEN SUPPLEMENTATION ON BACTERIOCIN PRODUCTION OF LACTIC ACID BACTERIA FROM PICKLED YELLOW BAMBOO SHOOTS (Dendrocalamus asper) - LAKSMI HARTAJANIE; LINDAYANI LINDAYANI; LORENTIA SANTOSO (Microbiology Indonesia, 2018)
Six selected lactic acid bacteria (LAB) isolates from pickled Yellow Betung bamboo shoots were grown in de Mann Rogosa Sharpe-Broth (MRSB) media with different supplementation combination. The cell-free supernatant were evaluated for their ability to produce bacteriocin by adjusting its pH to 6.0 in order to remove organic acid effects. The bacteriocin activity was assayed by agar-well diffusion method. The inhibitory activity calculated in Activity Unit (AU in mm2 mL-1) of bacteriocins. The aims of this paper is to explore the effect of different medium compositions on bacteriocin production and its inhibitory activity against pathogenic bacteria (Listeria monocytogenes FNCC 0156, Staphylococcus aureus FNCC 0047, and Escherichia coli FNCC 0091).Supplementations of carbon and nitrogen sources induced production of bacteriocins. LAB isolates grown in media without supplementation could not produce bacteriocins. Growth of isolate D44 in the presence of 2% of glucose and 2% of yeast extract yielded the largest bacteriocin inhibitory activity levels of 3179 AU mL-1 against Listeria monocytogenes FNCC 0156, 4663 AU mL-1 against Staphylococcus aureus FNCC 0047, and 3109 AU mL-1 against Escherichia coli FNCC 0091.